Beyond the Crisis: Financial Regulatory Reform in Emerging Asia - Chee Sung Lee; Cyn-Young Park (Asian Development Bank (ADB), 2009)
The main objective of this paper is to suggest reform measures to address the gaps and weaknesses in emerging Asia's financial regulatory and supervisory systems, on the basis of lessons drawn from the global crisis. For emerging Asia, the direct impact of the global financial crisis has been limited, thus generating substantially less pressure for financial restructuring and regulatory reform than is the case in developed economies. However, the underlying causes of the current turmoil—such as the dynamics of financial innovation and globalization—remain relevant for the region. As the world embraces wide-ranging financial reforms, emerging Asia will face dramatic changes in the global financial landscape. The region's authorities need to be prepared for the changing regulatory environment and proactive in strengthening their national regulatory and supervisory frameworks, in line with higher regulatory standards emanating from global reforms. Financial regulators will also need to design an effective and coherent framework for cross-border crisis management, and work towards a potential international regulatory and surveillance system.
hdl:11540/1825
Keywords: G01; G28; 330; Financial regulation; regulatory reform; asia; global financial crisis